(untitled) (Research, Society and Development, 2022)
Objective: Identify how information and communication technology tools are used by health institutions during the patient’s journey. Method: This is an integrative review, carried out in August and September 2022, in the scientific bases SCOPUS, EMBASE, PUBMED, BMJ JOURNALS, INPI and IEEE. The descriptors patient, information technology and hospital were used, articulated by the Boolean operator “AND”. The selection of studies was selected by selecting the titles, reading the abstracts and, finally, analyzing the entire publication. Results: Articles published between 2019 and 2021 were selected. Despite having been informed in the literature2019 and informed about the volume of articles related to health communication in the form of technological tools. The selected articles addressed the development of applications as a way to contribute to the health condition of patients and/or reduce health. Conclusion: There is a communication of studies carried out on technological tools and information between patients and professionals. The importance of an effective management of health appointments is highlighted.